Risk management and cultural virtue in HE co-delivery arrangements. Issue 2 (1st April 2014) - Talbot, Jonathan; Perrin, David; Meakin, Denise
Abstract : Purpose: – The purpose of the paper is to contribute to the debate on the maintenance and enhancement of quality in the emerging landscape of higher education practice and delivery where new kinds of institutional relationships are emerging. Much of the literature describes situations where the risk to quality assurance is relatively low. The example discussed here details how principles of risk management can be used to assure quality where the risk of reputational damage is far greater. Design/methodology/approach: – The paper uses a single case study approach. Findings: – New and flexible forms of delivery in higher education present opportunities but also the potential for reputational damage so innovative delivery must be matched by a corresponding commitment to quality. This must be embedded at all levels, including tutors. Much of the literature from the perspective of tutors emphasises their experience of quality as a matter of bureaucratic compliance. The case study illustrates that in circumstances where there is a risk of compromise academic tutors can actively engage with a quality enhancement process. Research limitations/implications: – Although a case study of specialised practice there is evidence that increasing numbers of universities are seeking to engage in similar methods. The literature on the implications of these initiatives is comprised of case studies so there is a need for more systematic research which examines practices more broadly. The case study also suggests that the search for quality cultures in HE may fruitfully investigate circumstances where quality has to be fought for rather than assumed. Practical implications: – The paper demonstrates that universities can deliver in flexible and innovative ways which do not compromise their reputation provided they risk assess the implications of each arrangement and develop appropriate procedures and practices at all levels of operation. Originality/value: – The case study is not the first of its kind to be published but it is the first to be published in the context of the quality assurance literature rather than the more specialist work based learning literature. It links developments within that specialist field to more mainstream discourses in the quality assurance literature. It also draws attention of a wider audience to some of the more innovative developments in British HE practice.